Technology Integration in the Mobile Communication Industry : A Review - Kulshrestha, Vishal; Jain, Kokil (Prabandhan: Indian Journal of Management, 2018)
The human society has been witnessing major changes in the economic, consumer, and the social behavior context brought about by the growth in mobile communication and mobile broadband and its increased adoption in all parts of the world. This paper analyzed these specific dimensions together and identified the relationship between them. Since the changes have been brought about by the advancement of mobile communication technology, the paper defined the nature of mobile technology and its components. Also, the paper defined how the technology in mobile was related to changes in human society. Finally, the paper outlined the reasons for the rapid growth in mobile technology and its ever accelerated adoption all over the world. The methodology used was a review of existing literature related to development in mobile technology and changes in social, economic, and consumer behavior due to expansion in mobile technology. The findings of the study showed that the mobile technology today stands for technology integration between technologies namely mobile network and infrastructure technology, mobile broadband and computing technology, and smartphone devices. Its development has impacted social, economic, and consumer behavior of the human society. The changes and development in human society have served as fuel for further progress in mobile technology. Therefore, it can be concluded that the development has been interrelated and has supported each other. This study will give a thorough understanding to managers of the influencing factors of service adoption and create an appreciation for investment in technology as an important strategic tool which will define the future competitive advantage.